Influence of blood pressure variability on early carotid atherosclerosis in hypertension with and without diabetes. Issue 24 (June 2016) - Wu, Dan; Li, Chunyue; Chen, Yujie; Xiong, Huahua; Tian, Xiaohong; Wu, Wanqing; Huang, Wenhua; Zhang, Yuan-Ting; Zhang, Heye
Abstract : Abstract: Carotid intima-media thickness (IMT) has been one widely used index of early carotid atherosclerosis. We speculated that the influence of blood pressure variability (BPV) on early carotid atherosclerosis may be varied by the location of the carotid artery and diabetes history. Thus, the goal of this study was to evaluate the effects of BPV on early arteriosclerosis progression in different segments of the carotid artery for hypertension with and without diabetes. A total of 148 hypertension patients who underwent 24 hours ambulatory blood pressure (BP) monitoring and carotid ultrasonography were enrolled in this study. Of them, 84 subjects were without diabetes, and 64 subjects were with diabetes. Short-term BPV during daytime, nighttime, and over 24 hours were evaluated through standard deviation (SD) and average real variability (ARV). We measured carotid IMT at left and right common carotid artery (CCA), carotid bulb, and the origin of the internal carotid artery (ICA). The associations between segment-specific measurements of carotid IMT and 24 hours ambulatory BPV were analyzed. We found that IMT at the common carotid artery (CCA-IMT) and IMT at the internal carotid artery (ICA-IMT) were more closely associated with BPV than was carotid bulb IMT. In addition, for all subjects, BPV was clearly associated with left CCA-IMT but not with right CCA-IMT. Furthermore, in diabetes patients, nighttime systolic BPV was independently related to mean CCA-IMT ( P < 0.01) and mean bulb IMT ( P < 0.01). In contrast, in nondiabetes patients, daytime and 24 hours systolic BPV was positively associated with mean CCA-IMT ( P < 0.05), but not independent after adjusting for baseline characteristics such as age and sex. The findings of our study indicate a segment-specific association between carotid IMT and 24 hours ambulatory BPV, and the associations also vary according to the diabetes history. We conclude that BPV plays a distinct role in early carotid arteriosclerosis progression within different segments of the carotid artery, especially for the hypertensions with and without diabetes.